Porcine antibody profiles of 33 Mycoplasma hyopneumoniae fusion proteins from M. hyopneumoniae natural infection but not vaccination. Issue 1 (15th December 2022) - Ning, Yaru; Yang, Yujiao; Tian, Yaqin; Zhang, Yun; Luo, Wenyi; Wen, Yukang; Zhou, Yaoqin; Ding, Honglei
Abstract: Background: Mycoplasma hyopneumoniae, the primary pathogen responsible for porcine enzootic pneumonia, reduces average daily weight gain and causes substantial economic losses to the pig industry worldwide. Vaccination is the most common strategy to control this disease but offers partial protection. Therefore, developing next‐generation vaccines by screening protective antigens is crucial. Objectives: The aim of this study was to evaluate the antibody response to 33 recombinant proteins in pigs naturally infected with M. hyopneumoniae . Methods: The genes encoding 33 (hypothetical) membrane proteins or secretory proteins were ligated into pGEX‐6P‐1, pGEX‐6P‐2, pGEX‐5X‐3 or pGEX‐4T‐3 vectors and transformed into Escherichia coli BL21(DE3) or E. coli XL‐1 Blue to construct recombinant bacteria and to express the recombinant proteins. The recombinant bacteria expressing the target proteins reacted with porcine convalescent sera and negative sera to screen immunodominant proteins by ELISA. Then, recombinant bacteria expressing immunodominant proteins were used to identify the discriminating immunodominant proteins that were recognised by convalescent sera nut not hyperimmune sera. Results: All recombinant bacteria could express the target recombinant proteins in soluble form. Twenty‐one proteins were shown to present immunodominant antigens, and four proteins were not recognised by convalescent sera. Moreover, six proteins were considered discriminating and reacted with convalescent sera but not with hyperimmune sera. Conclusions: The identified immunodominant proteins were antigenic and expressed during bacterial infection, suggesting that these proteins, especially those capable of discriminating between sera, can be used to identify protective antigens with the view to develop more effective vaccines against M. hyopneumoniae infection. Abstract : Thirty‐three M. hyopneumoniae fusion proteins were expressed in soluble form. Twenty‐one immunodominant proteins were identified, and six discriminating ones reacted with convalescent but not hyperimmune sera were confirmed. The result provides candidate antigens for the exploration of protective antigens.